EMPLOYER ATTRACTIVENESS: The value of environmental practices of organizations - Fernandes, M.; Duarte, A.; Trindade, G. (4th Symposium on Ethics and Social Responsibility Research 2017, 2017)
In today's world, there is a great sense of urgency for companies to implement environmentally responsible practices. Natural resources decrease every day at a worrying speed and we may be facing an irreversible scenario where the sustain-ability of the natural resources essential to life are hopelessly compromised (Unit-ed Nations, 2002). In order to accelerate the incorporation of environmental prac-tices it is necessary that organizations perceive environmental practices as an asset to the business. This research focuses on the relationships between organizational dimensions, such as environmental practices and attractiveness factors of organi-zations as employers as well as the effects that individual dimensions have in the relationship between the organizational dimensions. The results from this study show that (1) one of the dimensions of attractiveness considered by workers is the "Environmental Value", meaning that an organization having a good reputa-tion for environmental responsibility, assuming a pro-environmental position and promoting and enhancing environmental programs is regarded as relevant and contributes positively to the evaluation of the organizations’ Employer Branding, (2) there is a positive relationship between the environmental practices of organi-zations and their attractiveness, and (3) environmental awareness and environ-mental behaviour in the workplace moderate the relationship between the organi-zational dimensions.